Strengthening Aswaja An-Nahdliyah to Anticipate Radicalism for Islamic Education Teacher Candidates - Jazil, Saiful; Fahmi, Muhammad; Hunaida, Wiwin Luqna; Rohman, Fathur; Djazilan, M. Sukron; Prasetia, Senata Adi; Sholihuddin, Muh.; Mas'ud, Ali (EDUKASIA, 2023)
This article examined the strengthening of Aswaja An-Nahdliyah’s understanding as an effort to anticipate radicalism for Islamic education teacher candidates at the Faculty of Tarbiyah, Sunan Ampel State Islamic University Surabaya. The type of this article was qualitative with a Participatory Action Research approach and the method of extracting initial condition data and coaching related to Aswaja An-Nahdliyah material as an effort to anticipate radicalism for Islamic education teacher candidates in the fifth semester of the Academic Year 2021-2022. The results demonstrated that strengthening Aswaja An-Nahdliyah provides an understanding of the map of radical groups and movements; Aswaja An-Nahdliyah teachings and attitudes teach religious moderation as a basis for anticipating and avoiding radicalism teachings and attitudes; Aswaja An-Nahdliyah’s teachings are full of religious tolerance, which helps to block radicalism. This issue is very important considering that even though Sunan Ampel State Islamic University Surabaya, as an Islamic university, is not free from radical infiltration, strengthening Aswaja is necessary to anticipate this, especially for Islamic education teacher candidates.